Can education change the world? Education amplifies differences in liberalization values and innovation between developed and developing countries. - Alain Van Hiel; Jasper Van Assche; David De Cremer; Emma Onraet; Dries Bostyn; Tessa Haesevoets; Arne Roets (PLoS ONE, 2018)
The present study investigated the relationship between level of education and liberalization values in large, representative samples administered in 96 countries around the world (total N = 139,991). These countries show meaningful variation in terms of the Human Development Index (HDI), ranging from very poor, developing countries to prosperous, developed countries. We found evidence of cross-level interactions, consistently showing that individuals' level of education was associated with an increase in their liberalization values in higher HDI societies, whereas this relationship was curbed in lower HDI countries. This enhanced liberalization mindset of individuals in high HDI countries, in turn, was related to better scores on national indices of innovation. We conclude that this 'education amplification effect' widens the gap between lower and higher HDI countries in terms of liberalized mentality and economic growth potential. Policy implications for how low HDI countries can counter this gap are discussed.